Integrating Bugis Cultural Values of Sipakatu, Sipakalebbi’, and Sipakainge’ into the Professional Code of Ethics for Accountants - Wina Ayudia Akbar; Febrina Nur Ramadhani; Lukman Dahlan (Vifada Management and Social Sciences, 2024)
This study aims to integrate Bugis cultural values Sipakatu, Sipakalebbi’, and Sipakainge’ into the professional code of ethics for accountants. Accountants’ ethical behavior plays a crucial role in determining the quality and reliability of financial reporting. Therefore, internalizing local ethical values may strengthen accountants’ commitment to professional standards and ethical conduct. This study employs a literature review method by analyzing 20 relevant scholarly articles retrieved from Google Scholar that align with the research objectives. The findings indicate that the principles of mutual humanization (Sipakatu), mutual respect (Sipakalebbi’), and mutual moral reminder (Sipakainge’) are highly relevant to the ethical dimensions of the accounting profession. These values contribute to fostering a harmonious and productive professional environment, enhancing motivation and performance through recognition of achievements, and ensuring accountability and compliance with ethical standards through continuous moral guidance. Accordingly, the integration of Bugis cultural values into the professional code of ethics for accountants requires systematic internalization within individual accountants to support ethical decision-making and professional integrity.